ANALISIS PENGARUH IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN (PNPM MP) TERHADAP PRODUKTIVITAS KERJA DAN KESEJAHTERAAN MASYARAKAT DI KECAMATAN DENPASAR UTARA - Mahendra, Putu Bayu Putra; Yasa, Nyoman Mahaendra; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
PNPM Independent Urban is one of the programs launched by the government. The program is implemen ted as a government effort to help the community by providing Direct Community Assistance (BLM),one of them is  Environment sector (infrastructure) of the National Program for Community Empowerment (PNPM) Independent urban for poverty alleviation with the hope that people can increase labor productivity in order to achieve prosperity.This study uses an intervening variable productivity of society through SEM Partial Least Square (PLS)analysis approach. The location of this study was performed in North Denpasar District. The population used is the recipient community of BLM PNPM Mandiri urban spread in 8 villages and three political district administered by a village chief consist of 98 people.The results showed that PNPM Independent Urban brings positive and significant impact on society productivity.
Keywords: BLM (PNPM) independent urban, work productivity, public welfare